Theory of Administrative Discretion: the Stages of Formation - O. N. Sherstoboev (Сибирское юридическое обозрение)
Administrative discretion is an important construction of modern administrative law, the formation of which in many respects can be viewed as a “struggle” to limit the discretionary powers of the subjects of state administration. It is well known that good governance would be impossible without administrative discretion. There are four stages in the development of the modern theory of administrative discretion and each stage was devoted to one aspect of this one but these stages did not coincide chronologically and developed in parallel. They had a different methodology, which was used by the founders and followers of the approaches prevailing at each stage. The first stage started in France and formed by the 18th century. This related to the concept of prudent governance exercised prudent officials who were ruled by enlightened monarch. Their decisions were not reviewed by the courts. The principle of reasonable is the modern result of this stage – an absolutely unreasonable administrative act is null and void. The second stage developed in parallel with the first one but formed by the 19th century. Administrative discretion was formed as legal concept on this stage, and it was presented as free discretion, which also could not be a subject to judicial review. The third stage, characterized by competition between administrative justice and free discretion, took place at the end of the 19th and the middle of the 20th. Judicial possibilities for reviewing discretionary acts gradually expanded, criteria for evaluating such acts were created. These criteria were incorporated into the laws and legal judicial positions after the fourth stage began. The creative side of discretion has become a very important part of this legal construction, administrative discretion at this stage is defined as a way of laws concretizing. Nowadays, the third and fourth stages are developing in parallel in Russia. It should be noted that the Russian administrative law doctrine was formed as a common doctrine Civil Law system. Russian authors always used the methodology of Civil Law system, developed it, but they paid attention to the specifics of our administrative law, our governing and historical development. Nevertheless, Russian doctrine needs more research in order to create more legally formalized administrative discretion. As a result, the legislature and courts should receive academic decisions suitable for implementation.